Air quality assessment in Algiers city - Belhout, Dalila (2018)
Very few studies related with the assessment and research of air pollutants have been initiated in Algiers, which is the political and economic capital of Algeria. This lack of studies is mainly due to the non-access and insufficiency of data, and also the failure of the air quality monitoring stations during the last years. For those reasons, the use of modeling tools can be useful to assess the air pollution levels and compare different control options. The main aim of this paper is to identify anthropogenic emission sources (road traffic, industrial, residential, and waste) which are considered key sources of air pollution in the greater Algiers, and to estimate the concentration levels of suspended particles with diameter ˂ 10 μm (PM10) and nitrogen dioxide (NO2) over the studied area during 2012. For this purpose, The Air Pollution Model (TAPM) was used. The results indicate that meteorology statistical measures present a perfect agreement between measured and predicted values. The index of agreement (IOA) for wind speed and its components is above 0.65, for temperature is 0.99, while for the air pollution, the comparison of predicted concentrations with measured ones shows similar results. The maximum concentration levels for PM10 (122 μg/m3) and for NO2 (91μg/m3) are higher than the values established by national and international legislation, and the industrial districts are more affected by air pollution than the urban areas.